Distribution of diagnostic imaging equipment in the Brazilian Unified Health System: an overview of Bahia state, Brazil (Brazilian Journal of Health Research, 2019)
Introduction: The Brazilian Unified Health System (SUS - Sistema Único de Saúde) is one of the most complete health systems in the world, although it has faced issues in the distribution of equipment and services throughout its history. Objective: Addressing the distribution of diagnostic imaging equipment within SUS, in Bahia State. Methods: Descriptive, exploratory study based on secondary data provided by the National Register of Health Facilities. Four diagnostic devices (conventional x-rays, mammography, tomography and resonance equipment) were selected to be investigated in the current study. They were subjected to descriptive analysis, based on calculations and information available in Ordinance N. 1631, from October 1st, 2015. Results: The distribution of X-ray equipment exceeded the mean expected for Bahia State. Mammography, tomography and magnetic resonance imaging equipment presented distribution deficit. This situation is similar to that of other Brazilian states, where the more advanced the equipment technology, the smaller the number of devices per inhabitant. Conclusion: Bahia State has deficient distribution of mammography, tomography and magnetic resonance imaging equipment and excessive number of conventional x-ray devices.